2022
DOI: 10.3390/jof8020159
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus—Host Interactions Mediating Airway Wall Remodelling in Asthma

Abstract: Asthma is a chronic heterogeneous respiratory condition that is mainly associated with sensitivity to airborne agents such as pollen, dust mite products and fungi. Key pathological features include increased airway inflammation and airway wall remodelling. In particular, goblet cell hyperplasia, combined with excess mucus secretion, impairs clearance of the inhaled foreign material. Furthermore, structural changes such as subepithelial fibrosis and increased smooth muscle hypertrophy collectively contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 132 publications
0
15
0
Order By: Relevance
“…Upon bronchial epithelial injury, activated epithelium secretes growth factors, including IL-13, IL-1b, TGF-b superfamily members, osteopontin and so on, all of which activate the underlying mesenchymal cell and, ultimately lead to basement membrane thickening, subepithelial fibrosis and smooth muscle hyperplasia (93). The recruitment of fibroblasts, the proliferation of these interstitial cells and other interstitial cells that form fibroblast foci, and the release of excessive extracellular matrix (ECM) components, such as fibronectin, collagen, hyaluronic acid, and proteoglycan, are characteristics of fibrosis and one of the important pathogenesis of pulmonary fibrosis and BO (94).…”
Section: Pyroptosis and Inflammationrelated Respiratory Diseases 21 S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Upon bronchial epithelial injury, activated epithelium secretes growth factors, including IL-13, IL-1b, TGF-b superfamily members, osteopontin and so on, all of which activate the underlying mesenchymal cell and, ultimately lead to basement membrane thickening, subepithelial fibrosis and smooth muscle hyperplasia (93). The recruitment of fibroblasts, the proliferation of these interstitial cells and other interstitial cells that form fibroblast foci, and the release of excessive extracellular matrix (ECM) components, such as fibronectin, collagen, hyaluronic acid, and proteoglycan, are characteristics of fibrosis and one of the important pathogenesis of pulmonary fibrosis and BO (94).…”
Section: Pyroptosis and Inflammationrelated Respiratory Diseases 21 S...mentioning
confidence: 99%
“…Pulmonary fibrosis is a deadly disorder characterized by a collection of ECM in interstitial tissue and basement membranes (94). There are respirable particles such as crystalline silica dust in many industries and occupations, studies have shown that the damage and persistent damage of residual persistent particles to pulmonary epithelial cells are driven by the inflammatory process, leading to lung diseases elicited by environmental exposures (eg, asbestosis and silicosis) (118).…”
Section: Pulmonary Fibrosis (Asbestosis Silicosis and Idiopathic Pulm...mentioning
confidence: 99%
“…Proteases from Aspergillus can disrupt epithelial integrity and disturb homeostasis and barrier function, culminating in an inflammatory response and consequently promoting disease in the individual [ 49 , 50 ]. A. fumigatus proteases are also described as a potential source for ECM component degradation [ 50 ], and most A. fumigatus allergens exert proteolytic activity. For example, Asp f 5 is a metalloprotease, while Asp f 13 and Asp f 18 are serine proteases [ 51 , 52 ].…”
Section: Aspergillusmentioning
confidence: 99%
“…Considered together, there is consistent evidence that A. fumigatus adheres to the epithelial surface by using a range of receptors and ECM components, activates different receptors, and modulates cell signaling pathways, culminating in inflammatory responses, in addition to affecting epithelial barrier integrity. However, how the initial response in respiratory epithelial cells against A. fumigatus drives the immune adaptive response and long-term epithelial remodeling events is still unclear [ 50 ].…”
Section: Aspergillusmentioning
confidence: 99%
“…Chronic exposure to allergens like HDM and Aspergillus fumigatus are now used to mimic airway remodeling in the context of allergic airway inflammation in murine model ( 46 49 ). Investigating A. fumigatus -induced airway remodeling led to the assumption that the asthmatic milieu provides optimal growth conditions for the fungus, whereby from A. fumigatus produced allergens and metabolic by-products could possibly destroy the integrity of the epithelium during germination Mimicking airway remodeling in murine models therefore may provide insight into the interactions of this fungus with the epithelium, but cannot provide information about the function of individual cell types in the epithelium during fungal infection ( 49 ). To mimic not only airway but also vascular remodeling in asthma, mice were sensitized with ovalbumin (OVA) leading to development of an IgE-mediated hyper-reactive airway disease.…”
Section: Introductionmentioning
confidence: 99%